Bio-inks for 3D extrusion-based bio-printed scaffolds: printability assessment - Passamai, Verónica (2019)
Three-dimensional bioprinting is a new technology that should be integrated into several areas, including medical technology. However, before designing and applying it on a large scale, several biophysical parameters and particularly printability need to be established. In the present work, general characteristics of the extrusion method, bioinks, and scaffolds are reviewed. Printability analysis of 3D bioprinting is also included.